2011
DOI: 10.1111/j.1439-0523.2011.01924.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTL for heat tolerance at flowering stage in rice using SNP markers

Abstract: To identify quantitative trait loci (QTL) controlling heat tolerance in rice, the progeny of BC 1 F 1 and F 2 populations derived from an IR64 · N22 cross were exposed to 38/24°C for 14 days at the flowering stage, and spikelet fertility was assessed. A custom 384-plex Illumina GoldenGate genotyping assay was used to genotype the F 2 and selected BC 1 F 1 plants. Four single nucleotide polymorphisms were associated with heat tolerance in the BC 1 F 1 population using selective genotyping and single marker anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
139
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(145 citation statements)
references
References 43 publications
6
139
0
Order By: Relevance
“…Such a common response mechanism is promising for the translation of findings from model species to crops. Unfortunately, comparison of the QTLs observed in this study with earlier identified QTLs in other mapping studies in crops aiming to identify heat tolerance genes during flowering is difficult because most QTLs have not been cloned yet (Grilli et al, 2007;Ye et al, 2012;Lucas et al, 2013). All earlier studies were done in low-resolution biparental mapping populations; therefore, the associated regions still contain many genes.…”
Section: Homology Of Heat Stress Responses Between Speciesmentioning
confidence: 89%
See 1 more Smart Citation
“…Such a common response mechanism is promising for the translation of findings from model species to crops. Unfortunately, comparison of the QTLs observed in this study with earlier identified QTLs in other mapping studies in crops aiming to identify heat tolerance genes during flowering is difficult because most QTLs have not been cloned yet (Grilli et al, 2007;Ye et al, 2012;Lucas et al, 2013). All earlier studies were done in low-resolution biparental mapping populations; therefore, the associated regions still contain many genes.…”
Section: Homology Of Heat Stress Responses Between Speciesmentioning
confidence: 89%
“…Moreover, such studies reveal the actual genetic regulators driving a specific response, in contrast to identifying transcriptional differences upon heat stress in gene expression studies, which identifies many downstream effects of the response. Biparental mapping populations have been developed and used for quantitative trait locus (QTL) mapping of heat tolerance in various crops, such as rice (Ye et al, 2012), cowpea (Vigna unguiculata) (Lucas et al, 2013), and tomato (Grilli et al, 2007). These studies identified multiple QTLs (from 2 to 18) with an explained variance between 2 and 20%.…”
Section: Introductionmentioning
confidence: 99%
“…Several QTLs have been mapped for heat tolerance at flowering stage (Ye et al 2011;Jagadish et al 2010a;Zhang et al 2008;Xiao et al 2011). In our study, RM250 and RM88 were associated with days to flowering in normal and poly cover house methods respectively but same type of alleles were observed in both susceptible and tolerant checks indicating they are not specific to a haplotype.…”
Section: Discussionmentioning
confidence: 43%
“…Exploring the thermo tolerance diversity in rice plants will provide useful information for the improvement of traits to cope with the projected climate warming scenarios in the future (IPCC: Intergovernmental panel on climate change 2007). The impact of heat stress on rice yield depends on the genotype, the growth stage at which heat stress is received and the period of the stress (Liao et al 2014;Poli et al 2013;Zhou et al 2012;Ye et al 2011;Jagadish et al 2010a;Prasad et al 2006;Morita et al 2005). In general, when rice plants are exposed to temperature greater than 35°C for more than one hour at anthesis, it results in increased sterility (Jagadish et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation